Dehydrogenation Performances of Different Al Source Composite Systems of 2LiBH4 + M (M = Al, LiAlH4, Li3AlH6) - Li, Yun; Wu, Shaolong; Zhu, Dongdong; He, Jun; Xiao, Xuezhang; Chen, Lixin (Frontiers in Chemistry, 2020)
Hydrogen has become a promising energy source due to its efficient and renewable properties. Although promising, hydrogen energy has not been in widespread use due to the lack of high-performance materials for hydrogen storage. Previous studies have shown that the addition of Al-based compounds to LiBH4 can create composites that have good properties for hydrogen storage. In this work, the dehydrogenation performances of different composite systems of 2LiBH4+ M (M = Al, LiAlH4, Li3AlH6) were investigated. Results show that, under a ball to powder ratio of 25:1 and rotation speed of 300 rpm, the optimum ball milling time is 50 h for synthesizing Li3AlH6 from LiH and LiAlH4. The three studied systems destabilized LiBH4 at relatively low temperature, while the 2LiBH4-Li3AlH6 composite demonstrated excellent behavior. Based on the differential scanning calorimetry results, pure LiBH4 released hydrogen at 469 ºC. The dehydrogenation temperature of LiBH4 is 416 ºC for 2LiBH4-Li3AlH6, versus 435 ºC for 2LiBH4-LiAlH4 and 445 ºC for 2LiBH4-Al composite. The 2LiBH4-Li3AlH6, 2LiBH4-LiAlH4, 2LiBH4-Al samples released 9.1 wt.%, 8 wt.%, and 5.7 wt.% of H2, respectively. Additionally, the 2LiBH4-Li3AlH6 composite released 9.1 wt.% H2 within 150 min. An increase in the kinetics was achieved. From the results, it was concluded that 2LiBH4-Li3AlH6 exhibits the best dehydrogenation performance. Therefore, the 2LiBH4-Li3AlH6 composite is a considered hydrogen storage material.